The story of Miss Moppet. 21 - Potter, Beatrix, 1866-1943 (Beatrix Potter : The Complete Collection of Original Tales 1-23 Peter Rabbit, 2002)
And because the Mouse has teased Miss Moppet - Miss Moppet thinks she will tease the Mouse.